(untitled) (The Research of Medical Science Review, 2025)
Background: Laparoscopic cholecystectomy (LC) is a widely performed procedure for gallbladder removal, typically done for conditions such as cholelithiasis and chronic cholecystitis. Objectives: To compare the SSI rates in patients undergoing LC with infraumbilical versus transumbilical port site approaches. Study Design & Setting: This study was conducted at the Department of Surgery, DHQ Teaching Hospital, Sargodha from16 September 2024 - 15 March 2025. Methodology: A total of 154 patients undergoing laparoscopic cholecystectomy were divided into two groups: Group A (Infraumbilical) and Group B (Transumbilical), with 77 patients in each group. Surgical site infection (SSI) rates were recorded postoperatively and compared between the two groups. Patients were stratified by age, BMI, ASA class, diabetes, and hypertension to assess their potential influence on SSI. Statistical analysis was performed using chi-square tests to determine significant differences in SSI rates. Results: The mean age in Group A was 45.2 ± 10.1 years, while in Group B it was 46.3 ± 9.8 years. Gender distribution was fairly balanced, with 51.9% males and 48.1% females in Group A, and 54.5% males and 45.5% females in Group B. Diabetes Mellitus was present in 24.7% of Group A and 25.9% of Group B, while 28.6% of Group A and 27.3% of Group B had hypertension. SSI rates were 5.2% in Group A (infraumbilical) and 9.65% in Group B (transumbilical), but the differences were not statistically significant (p > 0.05). Stratified analysis revealed no significant effect of age, BMI, ASA class, diabetes, or hypertension on SSI rates. Conclusion: No significant difference in SSI rates was found between the infraumbilical and transumbilical approaches. Other factors, such as age, BMI, and comorbidities, did not significantly affect the SSI outcomes.